Needs to effectively carry out ecological restoration processes in Ecuador - Mazón, Marina; Samaniego, Natalia; Ojeda-Luna, Tatiana; Eguiguren, Paúl; Veintimilla, Darío; Maita-Chamba, Juan (BOSQUE, 2023)
During the Third Ecuadorian National Congress on Landscape Restoration (CERP 2021), the Tropical Research Center on Environment and Biodiversity of the Universidad Nacional de Loja organized a workshop to promote dialog to discuss the ecological restoration needs that the country must address. The workshop relied on the virtual presence of participants from NGOs, governmental organizations, private enterprises, local farmers, and researchers, as well as about 100 attendees, who also presented their opinions in the virtual platform. According to the participants, the priorities in Ecuador are: i) creation of manuals for identification of suitable perennial plant species in every Ecuadorian ecosystem and in accordance with the specific restoration goals, ii) a compilation of restoration techniques (considering the ecosystem and local knowledge), iii) inclusion of non-vascular plants from early successional stages, iv) exploration of plant-animal interactions, v) monitoring of restoration practices, vi) inclusion of the socioeconomic aspects of restoration, vii) incorporation of the forest landscape restoration approach, viii) research of propagation strategies, ix) evaluation of effectiveness of policies and laws regarding restoration, and x) improving compatibility of restoration with productive activities. Participants proposed the compilation of all research priorities in a national research agenda on restoration, and the significant improvement of knowledge transfer and dissemination.